The Relationship Between Nocturnal Blood Pressure and Hemorrhagic Stroke in Chinese Hypertensive Patients. Issue 9 (24th July 2014) - Sun, Jialan; Yang, Wanlin; Zhu, Yang; Liu, Xiaohong; Wei, Xin; Wang, Baisong; Zhong, Jiuchang; Fu, Yi
<x xml:space="preserve">Abstract</x> To study the relationship between nocturnal blood pressure (BP) variation and spontaneous intracerebral hemorrhage (ICH) among Chinese hypertensive patients and its clinical significance, the authors retrospectively screened 371 patients with primary hypertension (189 patients with ICH, 182 patients without ICH) in Shanghai and analyzed their demographics, clinical information, nocturnal blood pressure variability and medication. Compared with the control group, the levels of blood glucose, triglycerides, and creatinine were significantly increased in the ICH group, along with a marked reduction in nocturnal BP drop (P<.05). Multivariate logistic regression indicated that blood glucose, creatinine, and nocturnal mean arterial pressure were risk factors for ICH, and the magnitude of nocturnal BP drop was negatively related to the risk for ICH. There was no significant difference in the prevalence of reverse dippers between the large hematoma volume group and the small hematoma volume group (χ2=2.529, P=.112), nor among the patients taking angiotensin‐converting enzyme inhibitors, angiotensin receptor blockers, or calcium channel blockers (χ2=1.981, P=.371). Reverse dipping is associated with the risk for ICH, suggesting that appropriate antihypertensive drug and chronotherapy might be effective to normalize the rhythm of abnormal circadian variation in hypertensive patients.